"I Can See a Clock Measurement Precision Advance by Another Factor of Ten": Jun Ye, awarded with the Norman F. Ramsey Prize 2019, talks about his research, his aims, and his visions. Issue 3 (24th May 2019) - Unknown
Abstract: The Norman F. Ramsey Prize in Atomic, Molecular, and Optical Physics 2019 by the American Physical Society was awarded to Dr. Jun Ye. He leads the AMO Physics and Precision Measurement research group at the Joint Institute for Laboratory Astrophysics (JILA) at the University of Colorado Boulder. He was recognized for his groundbreaking contributions to precision measurements and the quantum control of atomic and molecular systems, including atomic clocks.